Purpose in the Broken: A Journey from Disillusion to Direction - de Broucker, Agathe (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2025)
This commentary explores the evolution of the sense of purpose for a mental health professional navigating the tensions between personal vocation and systemic realities. With a tale of lived experience, the author dives into the dissonance she once felt between the values that drew her into the helping field and the institutional conditions that often undermine them. With empathy for the individual workers, the piece critically examines how systems shape care and credibility, while affirming the importance of compassion, creativity and collective purpose. Grounded in a commitment to remain present in the field, the essay calls for a more trauma-informed, sustainable practice of the helping professions - one that values both the providers and the people they serve.